2016
DOI: 10.12988/bmgt.2016.639
|View full text |Cite
|
Sign up to set email alerts
|

Elevated galectin-3 level predicts pulmonary artery hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a heterogenic group of devastating disorders that characterizes higher rates of mortality and morbidity worldwide. Recent clinical studies have shown that clinical features, hemodynamic parameters, echocardiography patter, multi-spiral computer tomography findings, exercise capacity, and anti-nuclear antibody profiles could be used as predictors of clinical severity and outcomes in PAH patients. However, the reliability, sensitivity, specificity and predictive value are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Gal-3 plasma levels are correlated with right ventricle dysfunction [ 358 ] and with extracellular matrix markers [ 356 , 357 ]. Gal-3 seems to play a key role in acute and chronic inflammatory responses to endothelial injury, vascular remodeling and fibrosis in PAH [ 359 ]. The serial measurement of Gal-3 serum levels was suggested as a useful marker to improve prediction and progression of PAH [ 360 ].…”
Section: Pmentioning
confidence: 99%
“…Gal-3 plasma levels are correlated with right ventricle dysfunction [ 358 ] and with extracellular matrix markers [ 356 , 357 ]. Gal-3 seems to play a key role in acute and chronic inflammatory responses to endothelial injury, vascular remodeling and fibrosis in PAH [ 359 ]. The serial measurement of Gal-3 serum levels was suggested as a useful marker to improve prediction and progression of PAH [ 360 ].…”
Section: Pmentioning
confidence: 99%
“…The heterogeneity of nature evolution, clinical features, prognosis, and treatment response supports the need for identifying PAH patients at risk with various methods [44]. Recent clinical studies have shown that clinical status, hemodynamics, several biomarkers (growth differentiation factor-15, interleukin-6, creatinine, and NT-proBNP levels) and exercise capacity may predict severity and clinical outcomes in selected cohorts of patients with PAH [11] including subjects with known cardiac dysfunction [45].…”
Section: Predictive Value Of Galectin-3 In Pahmentioning
confidence: 99%